Development of TikTok Application-Based Learning Media on Environmental Change Material for class X SMA Negeri 1 Gorontalo - Sri Agustina Ilahude; Abubakar Sidik Katili; Chairunnisah J. Lamangantjo (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
This research aims to develop learning media for Environmental Change material based on the TikTok application for class X students at SMA Negeri 1 in Gorontalo. This research is development research using the ADDIE model with trials on 20 students. This research analyzes data on learning media development, namely data analysis of validity, practicality, and effectiveness. The research results showed that (1) The media validity test based on percentages obtained a score of 95.8% (Very Valid), and the material validity test based on percentages obtained a score of 86% (Very Valid), (2) The Practicality Test consisted of Student Responses and Teacher Response. The student response test obtained a score of 83% (Very Practical), and the Teacher Response test obtained 90% (Very Practical). (3) The student learning outcomes test was obtained from the Pretest and Posttest evaluation results, based on the N-Gain scale, obtaining a score of 0.57 which is included in the (Medium) category. Based on the results of trials developing the TikTok media, it is categorized as valid, practical, and effective for use in classroom learning.